Informal urbanism and the waste economy a case study on the informal production of charcoal at ulingan in the Tondo Bay Area - Sicam, Olivia Alma G. (College of Architecture, University of the Philippines Diliman, 2016)
Existing and expanding urban systems, infrastructure, and functions offer a multitude of economic opportunities for the informal sector. The resulting informal economy, in turn, provides goods and services to the city that have become part of the urban environment. Waste-a by-product of the city- plays an important role in the social geography and urban form of Manila by providing places of economic opportunity for informal settlements to flourish. The emergence of scavenger communities in dumpsites is a common, if not natural, occurrence. An informal community in the Tondo Bay Area engaged in the waste economy was examined in order to determine the means by which informality adapts to changes in the urban environment. The study focused on an informal settlement community inside the Vistas Reclamation Project site owned by the NHA called, "Ulingan", derived from the word uling, which means charcoal. Ulingan was a small informal settlement located along the breakwater of the lot, demolished in 2014, that was engaged in the collective production of charcoal using wood debris, a product of waste, as the raw material. The study involved key informant interviews, systematic observation, and secondary data collection for a time period that spanned three (3) and a half years, from the last year of charcoal production in 2013, during eviction of the community in 2014, and after its demolition in 2016. Urban form in the pre-demolition and post-demolition phases of the community was assessed by evaluating coherence (spatial organization), connections (socio-economic networks), and context (associative meanings). The study argued that, in the context of the Tondo Bay Area, informal urbanism is the process by which urbanization occurs instinctively and responsively to the urban environment correlating to formal frameworks of development. The adaptive and resilient qualities of informal settlements in this area, as demonstrated by Ulingan, are translated in space as movement, mutually-reinforcing networks, and places that hold meaning and associations.